A Project-Based Assessment Model of English for Senior High School Grade X - Hanardi, Levyn Gracia (Indonesian Journal of English Language Studies (IJELS), 2015)
Related to the implementation of the Curriculum 2013, project-based learning becomes one of the learning models that should be implemented in teaching and learning activities. Hence,outcome-based assessment and authentic assessment are considered appropriate model forproject-based learning because they are based on activities that represent a real-life setting.The purpose of this article is to develop an alternative model of project-based assessmentsthat are related to the implementation of the Curriculum 2013. This model is related to thebasic competences and objective of the lesson unit. Designed from concepts of project-basedlearning, authentic assessmemnt and outcome-based assessment, this project-basedassessment model can be one example of improvement of life quality in English languagelearning. It is hoped that the project-based assessment model will improve a betterunderstanding of the needs of students because it offers students‘ opportunity to investigateand discover authentic topics of interest. Using this model of project-based assessment,students‘ engagement in learning process can be improved.Keywords: project-based assessment, outcome-based assessment, authentic assessment gradeX of senior high school.